Frequency Dynamics of Power Systems with Inertial Response Support from Wind Generation - Bruno Augusto Bastiani; Ricardo Vasques de Oliveira (Energies, 2023)
Inertial response support from wind turbine generators has become a priority requirement in most grid codes to improve the frequency response and frequency stability margins of power systems. However, the interaction between MPPT and inertial controllers may significantly degrade the power system dynamics. Therefore, there is a need to comprehensively understand the electromechanical dynamics of power systems with high penetration of wind generation. In this context, this work proposes a simplified dynamic model to assess the electromechanical dynamics of modern power systems with inertial response support from wind generation. The proposed simplified model allows simple analyses of the intrinsic and extrinsic aspects of wind generation that directly affect the system frequency dynamics and the dynamics of wind turbine generators. As a secondary contribution, this work also provides a comprehensive assessment of intrinsic and extrinsic aspects of wind generation that significantly affect the electromechanical dynamics of power systems with inertial response support from wind generation.